Answer: To find the inverse of the function, we need to make x as a function of y and at the final step make a switch between x and y (i.e. make x as y and y as x)
y = x² + 4x + 4 ⇒⇒⇒ factor the quadratic equation
y = (x+2)(x+2)
y = (x+2)² ⇒⇒⇒ take the square root to both sides
√y = x+2
x = √y - 2 ⇒⇒⇒ x becomes a function of y
final step:
∴ y = √x - 2 ⇒⇒⇒ the inverse of the given function
So, as a conclusion:
f(x) = y = x² + 4x + 4 ⇒⇒⇒ the given function
f⁻¹(x) = y = √x - 2 ⇒⇒⇒ the inverse of the given function
Answer:
Step-by-step explanation:
Answer:
3x^2 (y^5)^1/4 which is the first choice
Explanation:
The fourth root means that the bracket under has the root has a power of 1/4.
So, the given expression is:
(81 * x^8 * y^5)^1/4
Now, we will distribute the power as follows:
(81 * x^8 * y^5)^1/4 = (81)^1/4 * (x^8)^1/4 * (y^5)^1/4
= 3 * x^2 * y^5/4
This expression is equivalent to:
3x^2 (y^5)^1/4 which is the first choice
Hope this helps :)
So first I would say, what if all of them were dimes, how far away would it be from $14?
So 92 coins * 10 cents = $9.20
So it's 4.80 dollars away from 14 dollars.
So if we were to switch one to a quarter, it would increase by 0.15 cents.
So we want to see how many increases we need to reach 4.80 dollars more.
4.80/0.15 = 32
So there are 32 quarters and 60 dimes.
Answer:
∛6859 ( = 19).
Step-by-step explanation:
6,859^1/3 = ∛6859 (the cube root of 6859).
Using a calculator we see that this = 19.